Mafia Inc.: When godfathers become entrepreneurs - Marco Le Moglie; Giuseppe Sorrenti (University of Zurich, Department of Economics, 2017)
We study the investment of criminal organizations in the legal economy. We focus on Italy, a country historically plagued by a conspicuous presence of mafia-type organizations. By using the exogenous credit contraction imposed by the 2007 financial crisis we highlight how the consequences for newly established enterprises have been less severe in areas with organized crime. Although criminal organizations are largely detrimental for local economic conditions, their economic activity might act as an economic stabilizer in the short-run, especially in a context of weak institutional presence. The investment in the legal economy allows criminal organizations to launder money, make profits, and raise social consensus through the provision of alternative sources of social insurance.
Keywords: K42; L26; 330; Mafia; organized crime; illegal enterprises; financial crisis